When God Closes the Megachurch: Penutupan Bait Allah Salomo dan Penyebaran Gereja ke Masyarakat Luas - Handayani, Dwi Maria (Veritas : Jurnal Teologi dan Pelayanan, 2023)
Church closures as a result of the COVID-19 pandemic were initially unexpected and difficult for many believers to accept. Many questions arose at that time: why did God allow this to happen? Believers searched for meaning and God’s intention through this event. Starting from this condition, the author uses the narrative of the closing of Solomon’s Temple as a foothold in finding the theological meaning of such an event. The author also explores what caused the closure of the Temple and what effects it had. Finally, the author draws some relevant conclusions as guidance for post-pandemic churches. The author proposes that just as God did not command the exiled Israelites in Babylon to rebuild the temple there, today’s churches should no longer focus on restoring what they once did, but instead focus on looking out for opportunities that open up in the society at large that we previously considered secular or worldly.